Adsorption/desorption of human serum albumin on hydroxyapatite: a critical analysis of the Langmuir model. - Mura-Galelli, M J (1991)
We studied the adsorption of human albumin onto synthetic hydroxyapatite, using a radiotracer technique and a special flow cell. Adsorption was studied under various conditions corresponding to different thermodynamic paths. It appears that (i) as is the usual case, the isotherms obtained within a short time range (a few hours) do not correspond to a true equilibrium situation; (ii) when the adsorption process is followed for longer times, which is necessary at low bulk concentrations, one always reaches the plateau surface adsorption; (iii) this plateau value is independent of the "history" of the adsorption process and corresponds well to the jamming limit predicted by the random sequential adsorption model; and (iv) surface denaturation, leading to enhanced surface binding and thus decreasing desorption constants, is the important phenomenon that can partly and qualitatively explain our observations. Its time dependence, however, remains to be clarified.